Lamanya Persalinan Kala I dan II pada Ibu Multipara dengan Apgar Score Bayi Baru Lahir - Halimatussakdiah Halimatussakdiah (AcTion: Aceh Nutrition Journal, 2017)
In the first stage of delivery, some obstacles are usually happened, including irregular contractions, inadequate duration, and unexpected contractions’ frequency. Consequently, the baby will have asphyxia and the duration of the first and the second stage of the childbrith process will be expanded. The objective of this study was to see the correlation between the duration of both deliveries’ stages on mother multigravida toward Newborn Apgar Score. The method of this study was an analytical correlation with a cross-sectional study. The sample was 35 mother obtained with consecutive sampling method. The data instrument was the observation from. The study was done on 5 and 20 August 2016 in Government Hospital Banda Aceh. The data was done analyzed with statistical test analysis using correlation computing devices. The result of the bivariate analysis showed that there is a correlation between the duration of the first stage of delivery with the first minute Apgar Score (p-value 0,010), fifth minute Apgar score (p-value 0,010), while the second stage with the first minute Apgar Score (p-value 0,000), fifth minute Apgar score (p-value 0,000). From this study, it is expected that the chosen of adequate intervention, the duration of delivery of the first and the second stage has not happened so that the asphyxia on the newborns are decreasing.Keywords: Apgar Score, labor, first and second stageKala I persalinan sering ditemukan hambatan atau kendala. Kendala tersebut antara lain kontraksi rahim yang irreguler, durasi kontraksi yang tidak adekuat dan frekuensi kontraksi yang irreguler sehingga bayi mengalami asfiksia dan menimbulkan perpanjangan waktu kala I dan II persalinan. Tujuan penelitian untuk mengetahui hubungan lamanya persalinan kala I dan II pada ibu bersalin multipara terhadap Apgar Score  Bayi baru lahir. Jenis penelitian Analitik Korelatif, dengan desain Cross Sectional study. Jumlah sampel 35 ibu bersalin multipara tehnik pengambilan sampel dengan metode Consecutive Sampling. Pengumpulan data  menggunakan lembar observasi. Penelitian dilakukan  tanggal 05 - 20 Agustus 2016 di Rumah Sakit Pemerintah Banda Aceh. Metode analisis data menggunakan uji Statistik Regresi Korelasi dianalisis menggunakan perangkat komputer. Hasil analisa bivariat menunjukan ada hubungan antara lama kala I dengan Apgar Score menit 1 (p-value 0,010), apgar score menit 5 (p-value 0,010), kala II dengan Apgar Score menit 1 (p-value 0,000), apgar score menit 5 (p-value 0,000). Diharapkan pemilihan tindakan yang tepat dapar mencegah lamanya persalinan pada kala I dan II dan tidak terjadi asfiksia pada bayi baru lahir.Kata kunci: Apgar score, kala I dan II, persalinan